2017 ASEE Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/1-2--28836
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Reasoning Difference between Civil and Mechanical Engineering Students in Learning Mechanics of Materials Course: A Case of Cross-sectional Inference

Abstract: Abstract.Despite the fact that Mechanics of Materials (MM) course is laden with spatial concepts, the role of spatial skills in the learning of MM course has not been investigated adequately. This study investigated the relationship between students' performances of the MM course measured by the Mechanics of Material Concept Inventory Test and their cross sectioning ability measured by the Santa Barbara Solids Test. Participants are the freshman and sophomore students mostly majoring in civil and mechanical en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 7 publications
0
5
1
Order By: Relevance
“…It may be possible that the ENGR Statics course has less mechanics concepts involved with cross sections while ENGT Strength of Materials course has mainly 2D orthogonal views of structural cross sections, thereby losing all depth cues associated with the 3D structures. This finding is contradictory to the result from a previous study carried out by the same author(s) [1]. The previous study found a significant positive correlation (ρ = 0.552 at p = 0.01) between SBST scores of mechanical engineering students and their performance in the Mechanics of Materials (MOM) course.…”
Section: "Is There Any Significant Difference Between Engr and Engt Scontrasting
confidence: 81%
See 1 more Smart Citation
“…It may be possible that the ENGR Statics course has less mechanics concepts involved with cross sections while ENGT Strength of Materials course has mainly 2D orthogonal views of structural cross sections, thereby losing all depth cues associated with the 3D structures. This finding is contradictory to the result from a previous study carried out by the same author(s) [1]. The previous study found a significant positive correlation (ρ = 0.552 at p = 0.01) between SBST scores of mechanical engineering students and their performance in the Mechanics of Materials (MOM) course.…”
Section: "Is There Any Significant Difference Between Engr and Engt Scontrasting
confidence: 81%
“…At (name of university), both these courses are required in the four-year programs in engineering (ENGR) with a concentration in mechanical engineering as well as engineering technology (ENGT) with a concentration in applied systems technology. A previous study in engineering mechanics [1] suggests that to master the SMC course content, besides physics and mathematical skills, students need to have a strong spatial ability to retrieve and interpret spatial information from engineering structures and produce efficient spatial reasoning for solving problems. Spatial ability is the cognitive capability that helps people to apprehend, maintain, and manipulate 3D objects in their mind and is considered as a set of several spatial ability factors [2,3,4].…”
Section: Introductionmentioning
confidence: 99%
“…A spatially demanding task that is common in biology, anatomy, and engineering is the ability to visualize the correspondence between 3D structures and their 2D cross sections [40][41][42]. Cohen and Hegarty [43] found moderate positive correlations between the ability to draw cross sections of novel anatomical-like forms and measures of mental rotation and perspective-taking ability.…”
Section: Studies Of Spatial Thinking In Other Stem Disciplinesmentioning
confidence: 99%
“…University students' spatial ability scores predicted their skill in identifying anatomical structures [41]. Ha and Brown [42] found that performance on a measure of crosssectioning ability among sophomore civil and aeronautical engineering students accounted for 53% of the variance on a mechanics of materials concept inventory. Mechanics of materials is an engineering topic that requires the ability to visualize and analyze the distribution of stress loads on cross sections of inclined planes.…”
Section: Studies Of Spatial Thinking In Other Stem Disciplinesmentioning
confidence: 99%
“…Spatial visualization ability is essential for success in many academic fields including in medicine (Cohen & Hegarty, 2007;Wanzel, Hamstra, Anastakis, Matsumoto, & Cusimano, 2002), dentistry (Schwibbe, Kothe, Hampe, & Konradt, 2016) and engineering (Ha & Brown, 2017). Two categories of spatial reasoning, as defined by Linn and Petersen (1985), are mental rotation and spatial visualization.…”
Section: Introductionmentioning
confidence: 99%